‘What the hell is water?’ How to use deliberate clinical inertia in common emergency department situations - Egerton-Warburton, Diana; Cullen, L.; Keijzers, G.; Fatovich, D. (Wiley-Blackwell Publishing Asia, 2018)
© 2018 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine Appropriate deliberate clinical inertia refers to the art of doing nothing as a positive clinical response. It includes shared decision-making to improve patient care with the use of clinical judgement. We discuss common clinical scenarios where the use of deliberate clinical inertia can occur. The insertion of peripheral intravenous cannulae, investigating patients with suspected renal colic and the investigation of low risk chest pain are all opportunities for the thoughtful clinician to ‘stand there’ and use effective patient communication to avoid low value tests and procedures. Awareness is key to identifying these opportunities to practice deliberate clinical inertia, as many of the situations may be so much a part of our environment that they are hidden in plain view.